Cold carcass weight, fat thickness, C measurement and longissimus dorsi depth for predicting the carcass composition of Rasa Aragonesa ewes with different body condition score - Delfa, Rafael (1991)
The precision of the use of cold carcass weight, fat thickness, C measurement and longissimus dorsi depth for predicting the carcass composition were determined in 52 adult Rasa Aragonesa ewes aged 10 (s.d. 2) years and ranging in body condition score (BCS) front 1.5 to 4.5. The cold carcass weight is the best predictor of intermuscular fat (1'=0.94) and the inclusion of the C measurement in multiple regression with the cold carcass weight estimates with accuracy the subcutaneous fat (r2=0.91). The pelvic and kidney fat can be predicted with the same precision by cold carcass weight in multiple regression with fat thickness or BCS (r2=0.86). 95% of the variation in total carcass fat was accounted for by variation in cold carcass weight and fat thickness. The best muscle carcass predictors were cold carcass weight in multiple regression with fat thickness or C measurement (r2=0.91).